Erector spinae plane block in laparoscopic cholecystectomy: technique, systematic review and meta-analysis - S.M. Chooklin; S.S. Chuklin (Медицина неотложных состояний)
Background. Although laparoscopic cholecystectomy is a minimally invasive procedure, it can cause moderate to severe postoperative pain. Regional block is increasingly used in surgery as part of postoperative multimodal analgesia. This meta-analysis aimed to evaluate the analgesic efficacy of erector spinae plane block (ESPB) in patients undergoing laparoscopic cholecystectomy. Materials and methods. We systematically searched PubMed/MEDLINE, Scopus, and Google Scholar up to 2025. All randomized controlled trials that compared the efficacy of ESPB with other types of blocks for relieving postoperative pain after laparoscopic cholecystectomy were included. The primary outcomes were pain scores at rest and on movement at 1–2, 6, 12, and 24 hours postoperatively, and intraoperative fentanyl dose. The secondary outcomes were total opioid consumption, first analgesia request time, and rates of postoperative nausea and vomiting. We analyzed all the data using RevMan 5.4.1 software. Results. A total of 31 randomized controlled trials were reviewed. Twenty-five studies were included in the meta-analysis, 16 of which compared ESPB with a no-block group, and 9 with the transversus abdominis plane (TAP) block. ESPB significantly reduced pain intensity in both static and dynamic states, intraoperative fentanyl requirements, 24-hour postoperative opioid consumption, and time to the first analgesia request compared with no-block group. There were no differences between groups in the incidence of nausea and vomiting. ESPB was more effective in reducing pain severity scores at rest in all measured postoperative time points except at 12 hours than TAP block, and on movement only at 6 hours. In addition, ESPB resulted in lower tramadol equivalent consumption within the first 24 hours and a longer time to the first request for additional analgesia compared with TAP block. There were no significant differences in the incidence of postoperative nausea and vomiting as well. Conclusions. Bilateral ultrasound-guided erector spinae plane block may be considered an effective option for postoperative analgesia in adults undergoing laparoscopic cholecystectomy. It is more effective than transverse abdominal plane block.